Waste Clearance in the Brain - Kaur, Jasleen; Fahmy, Lara M.; Davoodi-Bojd, Esmaeil; Zhang, Li; Ding, Guangliang; Hu, Jiani; Zhang, Zhenggang; Chopp, Michael; Jiang, Quan (Frontiers in Neuroanatomy, 2021)
Waste clearance (WC) is an essential process for brain homeostasis, which is required for the proper and healthy functioning of all cerebrovascular and parenchymal brain cells. This review features our current understanding of brain WC, both within and external to the brain parenchyma. We describe the interplay of the blood-brain barrier (BBB), interstitial fluid (ISF), and perivascular spaces within the brain parenchyma for brain WC directly into the blood and/or cerebrospinal fluid (CSF). We also discuss the relevant role of the CSF and its exit routes in mediating WC. Recent discoveries of the glymphatic system and meningeal lymphatic vessels, and their relevance to brain WC are highlighted. Controversies related to brain WC research and potential future directions are presented.